Central Sensitization and Its Role in Persistent Pain Among Spondyloarthritis Patients on Biological Treatments - Nuran Öz; Aygün Özer; Mehmet Tuncay Duruöz (Medicina)
Objectives: Spondyloarthritis (SpA) is a chronic inflammatory arthritis that mainly affects the sacroiliac joints and spine. Despite effective biological treatments, persistent pain is common in SpA patients, potentially due to central sensitization (CS), a condition of heightened central nervous system responsiveness. The purpose of this study was to investigate the link between disease activity and CS in SpA patients on biological therapy. Patients and Methods: One hundred and twenty SpA patients with at least six months of treatment with biological agents were included in this cross-sectional study. Patients’ demographic, clinical, and functional information were collected. The assessment of CS was conducted using the Central Sensitization Inventory (CSI), whereas disease activity and quality of life were evaluated using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS)-C-reactive protein (CRP), and Ankylosing Spondylitis Quality of Life (ASQoL). Statistical analyses included correlation assessments and logistic regression to identify predictors of CS. Results: CS (CSI ≥ 40) was present in 40.8% of patients. Disease activity was significantly higher and quality of life was lower in patients with CS. BASDAI and ASQoL scores were strongly correlated with CS (r = 0.774 and r = 0.839, respectively). Logistic regression identified ASQoL and BASDAI scores as independent predictors of CS. ROC curve analysis demonstrated that ASQoL had the highest discriminative ability for predicting CS (AUC = 0.97). Conclusions: CS is significantly associated with higher disease activity and poorer quality of life in SpA patients receiving biological therapy. Incorporating CS assessment into routine clinical practice may enhance our understanding and management of persistent symptoms in SpA, improving patient outcomes.